Baristas, Products, Store Atmosphere, Prices, Social Media, And Consumer Satisfaction Coffee Shop In The Lowlands - Ajran Auyaghlib; Dini Azhari; Fathia Al Zaitun; Wachdijono Wachdijono (Journal Of Social Science (JoSS), 2023)
Coffee shop business opportunities show a positive trend, encouraging business actors to set up new coffee shops. The growth of coffee shops causes competition to become increasingly high. Therefore, coffee shop management must strengthen the main variables in its business. The main variables in a coffee shop include barista, product, price, atmosphere, social media, and customer satisfaction. This research aims to determine and describe the variable conditions of barista, product, price, atmosphere, social media, and consumer satisfaction. The research location is Tangerang City, Banten Province, Republic of Indonesia, considering that the area is included in lowland topography and many modern coffee shops are standing. The research was conducted in July-September 2023 with a sample size of 131 respondents. The research design is descriptive, using survey methods. Data analysis uses confirmatory factor analysis (CFA) instruments and the calculation of variable scores, which are compared with expected scores. The research results show that the condition of the barista is in the very skilled category (83.57%), the condition of the product is in the outstanding category (82.33%), the condition of the coffee shop atmosphere is in the very comfortable category (83.77%), the condition of the price is in the very affordable category (83.17%), social media conditions are in the outstanding category (81.76%), and consumer satisfaction conditions are in the very satisfied category (81.50%). The results of this research are very useful in planning/determining coffee shop business management strategies to win competition in the lowlands.